Staging process : the aesthetic politics of collective performance - Anderson-Rabern, Rachel (Northwestern University Press, 2020)
"This book of performance criticism studies the creative output of several performance artists and collectives through the theoretical lens of twentieth-century philosophical work on artistic gesture, spectacle, and collaboration"--